Voltage supply and voltage regulation - Torla, Ahmad Lutfi; Khan, Sheroz; Abdul Muthalif, Asan Gani (IIUM Press, 2011)
A stable voltage supply is important for the proper operation of electronic devices. Stability is characterized by the ability of the voltage output to stay constant and ripplefree regardless of how much load is connected to the circuit. There is a brief discussion on how much inaccuracy is caused by voltage supplies which are prone to voltage fluctuations due to switching phenomenon taking place in the circuit, load fluctuations or temperature changes